EVALUATION OF THE USE AND SOIL COVER OF THE SUB-BASIN OF THE ANAJÁ RIVER IN PAÇO DO LUMIAR-MA/BR - de Oliveira Borges, Jordane (2021)
The present study aimed to delimit the area of the Anajá River Sub-basin, analyze the land use and land cover with the aid of free geotechnologies. The applied methodology consisted in the use of GIS and Qgis Spring, for drainage and thematic maps of Land use and cover, and collecting points through GPS-Global Positioning System. The results indicate that the Anajá River Sub-basin has a third-order canal which originates at an altitude between 50 and 60 m. In which 8 classes of land use and cover were identified . The adoption of GIS allowed the automatic delineation of the area of the Sub-basin of the river Anajá, and quantification of the classes of use and coverage of the Earth, in addition to stating that the areas of urban buildings and farm type crops occupy much of this sub-basin. The present study aimed to delimit the area of the Anajá River Sub-basin, analyze the land use and land cover with the aid of free geotechnologies. The applied methodology consisted in the use of GIS and Qgis Spring, for drainage and thematic maps of Land use and cover, and collecting points through GPS-Global Positioning System. The results indicate that the Anajá River Sub-basin has a third-order canal which originates at an altitude between 50 and 60 m. In which 8 classes of land use and cover were identified . The adoption of GIS allowed the automatic delineation of the area of the Sub-basin of the river Anajá, and quantification of the classes of use and coverage of the Earth, in addition to stating that the areas of urban buildings and farm type crops occupy much of this sub-basin.